2015
DOI: 10.1152/ajpheart.00801.2014
|View full text |Cite
|
Sign up to set email alerts
|

GABA and glycine receptors in the nucleus ambiguus mediate tachycardia elicited by chemical stimulation of the hypothalamic arcuate nucleus

Abstract: elicits tachycardia, which is partially mediated via inhibition of vagal inputs to the heart. The neuronal pools and neurotransmitters in them mediating tachycardia elicited from the ARCN have not been identified. We tested the hypothesis that the tachycardia elicited from the ARCN may be mediated by inhibitory neurotransmitters in the nucleus ambiguus (nAmb). Experiments were done in urethane-anesthetized, artificially ventilated, male Wistar rats. In separate groups of rats, unilateral and bilateral microinj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The NTS receives primary information from cardiorespiratory sensory neurons, and the excitatory pathway from the NTS to CVNs likely plays an essential role in the chemoreceptor and baroreceptor reflex control of heart rate (1). Retrograde tracing studies have demonstrated direct projections from the PVN to the NA (6,22). This long-range neurotransmission from the PVN is excitatory with the endogenous release of oxytocin facilitating glutamatergic neurotransmission and excitation of CVNs (30).…”
Section: Discussionmentioning
confidence: 99%
“…The NTS receives primary information from cardiorespiratory sensory neurons, and the excitatory pathway from the NTS to CVNs likely plays an essential role in the chemoreceptor and baroreceptor reflex control of heart rate (1). Retrograde tracing studies have demonstrated direct projections from the PVN to the NA (6,22). This long-range neurotransmission from the PVN is excitatory with the endogenous release of oxytocin facilitating glutamatergic neurotransmission and excitation of CVNs (30).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction has been demonstrated only in animal models and should be explored in humans with the aid of UHF fMRI. The NTS/NAmb link is also influenced by tonic inhibitory influence from arcuate and paraventricular (PVN) hypothalamic nuclei onto NAmb (Ciriello et al 2003; Chitravanshi et al 2015), forming the core central control circuitry for cardiovagal modulation. Furthermore, NTS and NAmb, as well as surrounding portions of the medullary reticular formation, have been physiologically defined as the dorsal medullary respiratory center (Kalia 1977), in addition to the Kölliker-Fuse nucleus in the pons and portions of the PAG in the midbrain (see section 3.5).…”
Section: Assessing Specific Brainstem Neural Circuitries With Uhf mentioning
confidence: 99%
“…The details of all the procedures used in the present study are reported in our earlier publications (3,13,22,23,39). Initially, the rats were anesthetized with inhalation of isoflurane (2-3% in 100% oxygen), using a vaporizer (Fluotec-3, Cyprane, UK).…”
Section: General Proceduresmentioning
confidence: 99%